Revitalization of the biodiversity and animal welfare in promoting Mini Zoo Taman Teruntum, Kuantan - Nizamuddin, Nabilah (2018)
This study discusses a final comprehensive design in revitalizing the biodiversity and animal welfare towards promoting Mini Zoo Taman Teruntum as a better zoological park in Kuantan. The zoological park can be defined as a park or institution in which living animals are kept and usually exhibited to the public that has facilities with recreational, education and conservation purpose towards wildlife protection. Due to the setting of the area which located as part of the reserve forest area, it influences the natural setting of the area as tropical rainforest. The topic for this study is to comprise all the environmental and zoological approach towards the revitalization of biodiversity and animal welfare while improving the human quality life within the zoo area. The methodology of this study involves the data collection of primary and secondary data, where the data will be analysed and its finding will be used in design development and proposal. Subsequently, with the concept of ‘Wild Gems’, the design strategy and ideas have been transformed into the physical form to showcase the precious and outstanding natural environment of wildlife habitat. The physical character of this study will emphasize on the space planning of the animal exhibit and public space with the systematic linkage and trail that connect one exhibit to another. While the environment context focuses on the implementation of plant selection in wildlife habitat that will give benefit towards their welfare and lifestyle. In order to cater the issues in the site, the objectives which to study the image, element, and management guidelines towards the liveability of the zoological park and to propose the best element of zoological park design that can create an interest among the public, towards animals and its surrounding has been defined. Hopefully, the findings from this project can be used not only as a design strategy and guideline but also as the reference to improving and enhancing the zoological park.